Social Context Matters: Predictors of Quality of Life among Recently Arrived Refugee Women-at-Risk Living in Australia. Issue 4 (1st October 2020) - Correa-Velez, Ignacio; Green, Aleana; Murray, Kate; Schweitzer, Robert D; Vromans, Lyn; Lenette, Caroline; Brough, Mark
Abstract: Little is known about the predictors of quality of life among refugee women. 104 refugee women-at-risk were recruited within 6 months of arriving in Australia. A structured questionnaire was administered using standardized tools to assess pre-migration trauma, post-migration living difficulties, social capital, social networks, and quality of life. Hierarchical multiple and logistic regressions assessed factors predicting quality of life. Post-migration factors such as low trust in the community, and lack of support from individuals in their social networks predicted poorer quality of life. These findings have implications for community and social programs for refugee women-at-risk.